Perennial rice: improving input efficiency for sustainable rice landscape in C?te d?Ivoire - CGIAR Research Program on Rice (2020)
We validated the performance of the perennial rice varieties PR23 and PR25 for reducing water use in rice cultivation and increasing rice yield compared with the annual high-yielding local variety in the research station of Africa Rice center in Mbe.